Hitler's Library - Miskolczy, Ambrus (Book collections on Project MUSE., 2003)
The first book that presents the so called Hitler-Library. It sheds new light on the readings of Hitler and on his techniques how to read a book. He played the role of the ideal reader of Schopenhauer, nevertheless his remarks destroy the image of the contemporary Hitler-cult, mainly if we see how he re-read his Mein Kampf. Hitler is presented in this book as a reader and it verifies the explication of his personality (Hitler as follower of Wagner, Hitler as philosopher, Hitler as crazy, Hitler as clever politician, Hitler as hero): it gives the picture of a half-educated gangster.